In vivo synaptic density loss is related to tau deposition in amnestic mild cognitive impairment. (4th August 2020) - Vanhaute, Heleen; Ceccarini, Jenny; Michiels, Laura; Koole, Michel; Sunaert, Stefan; Lemmens, Robin; Triau, Eric; Emsell, Louise; Vandenbulcke, Mathieu; Van Laere, Koen
Abstract : Objective: To investigate in vivo whether synaptic loss and neurofibrillary tangle load spatially overlap and correlate with clinical symptoms in patients with amnestic mild cognitive impairment (aMCI). Methods: In this cross-sectional study, 10 patients with aMCI and 10 healthy controls underwent triple PET-MRI with 11 C-UCB-J (synaptic vesicle protein 2A), 18 F-MK-6240 (tau deposition), and 11 C-Pittsburgh compound B (β-amyloid) and neuropsychological assessment. Gray matter atrophy was assessed by voxel-based morphometry with T1-weighted MRIs. Voxel-wise and volume-of-interest analyses were conducted on PET data. The interrelationship of synaptic density and tau deposition was investigated. We also investigated correlations of 18 F-MK-6240 and 11 C-UCB-J binding with cognitive performance. Results: Compared to controls, patients with aMCI showed a decreased 11 C-UCB-J binding mainly in substructures of the medial temporal lobe (MTL; 48%–51%, p cluster = 0.02). Increased 18 F-MK6240 binding in the same region was observed (42%–44%, p cluster = 0.0003), spreading to association cortices. In the MTL, higher 18 F-MK-6240 binding inversely related to lower 11 C-UCB-J binding ( p = 0.02, r = −0.76). Decreased performance on cognitive tests was associated with both increased 18 F-MK-6240 and decreased 11 C-UCB-J binding in the hippocampus ( p < 0.01, r > 0.7), although in a multivariate analysis only 18 F-MK-6240 binding was significantly related to cognitive performance. Conclusions: Patients with aMCI have high tau deposition and synaptic density loss mainly in key regions known to be involved in early cognitive impairment, indicating that these are interrelated in the MTL, while tau binding had already spread toward association cortices. Longitudinal data are needed to provide further insight into the temporal aspects of this relationship.